Information and Decision Sciences Proceedings of the 6th International Conference on FICTA - Satapathy, Suresh Chandra; Tavares, Joao Manuel R.S.; Bhateja, Vikrant; Mohanty, J. R.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents the proceedings of the 6th International Conference on Frontiers of Intelligent Computing: Theory and Applications (FICTA-2017), held in Bhubaneswar, Odisha. The event brought together researchers, scientists, engineers, and practitioners to exchange their new ideas and experiences in the domain of intelligent computing theories with prospective applications to various engineering disciplines. The book is divided into two volumes: Information and Decision Sciences, and Intelligent Engineering Informatics. This volume covers broad areas of Information and Decision Sciences, with papers exploring both the theoretical and practical aspects of data-intensive computing, data mining, evolutionary computation, knowledge management & networks, sensor networks, signal processing, wireless networks, protocols & architectures etc. The book also offers a valuable resource for students at the post-graduate level in various engineering disciplines.
1. A New Approach for Authorship Attribution -- 2. Using Aadhaar for continuous test-taker presence verification in online exams -- 3. Determining the Popularity of Political Parties Using Twitter Sentiment Analysis -- 4. Analysis on Passenger Flow Prediction of Transit Buses along a Route Based on Time Series -- 5. Smart Fire Safety: Serious Game for Fire Safety Awareness -- 6. An OpenMP based algorithmic optimization for Congestion Control of Network Traffic -- 7. Comparative analysis of frequent pattern mining for large data using FP-tree and CP-tree methods -- 8. Wireless Seatbelt Latch Status Indicator -- 9. A Study of Various Varieties of Distributed Data Mining Architectures -- 10. Graph Representation of Multiple Misconceptions -- 11. Classification through Discriminant Analysis over Educational Dataset -- 12. Dynamic and Secure Authentication Using IKC for Distributed Cloud Environment -- 13. Planned Random Algorithm -- 14. Hurst Exponent as a New Ingredient to Parametric Feature Set for Mental Task Classification -- 15. A Crawler-Parser Based Approach to Newspaper Scraping and Reverse Searching of Desired Articles -- 16. Impact of Cloud Accountability on Clinical Architecture and Acceptance of Health Care System -- 17. A Stability Analysis of Inverted Pendulum System Using Fractional Order MIT Rule of MARC Controller Using Fractional Order MIT Rule of MARC Controller -- 18. KMDT: A Hybrid Cluster Approach for Anomaly Detection using Big Data -- 19. Extraction and Sequencing of Keywords from Twitter -- 20. A Modular Approach for Social Media Text Normalization -- 21. Author Verification using Rich set of Linguistic Features -- 22. Deterministic and Randomized Heuristic Algorithms for Uncapacitated Facility Location Problem -- 23. Group Search Optimization Technique for Multi-area Economic Dispatch -- 24. Adaptive control of aircraft wing oscillations with stiffness and damping nonlinearities in pitching mode -- 25. Application of Total Least Squares Version of ESPRIT Algorithm for Seismic Signal Processing -- 26. Metadata Based Semantic Query in Multi Lingual Databases -- 27. A Step towards Internet Anonymity Minimization: Cyber-crime Investigation Process Perspective -- 28. Comparison of Different Fuzzy Clustering Algorithms: A Replicated Case Study -- 29. Passive Object Tracking Using Mgekf Algorithm -- 30. Instantaneous Time Smoothing In GPS Receivers Using Kalman Filter -- 31. Application of Least Squares Algorithm for Precise GPS Receiver Positioning -- 32. Application of parametric methods for earthquake precursors using GPS TEC -- 33. A Fuzzy-based Modified Gain Adaptive Scheme for Model Reference Adaptive Control -- 34. Early System Test Effort Estimation Automation for Object Oriented Systems -- 35. Identification of Co-seismic signatures by comparing Welch and Burg methods using GPS TEC -- 36. Energy Efficient GPS Usage in Location based Applications -- 37. Group Recommender Systems-Evolutionary Approach based on consensus with ties -- 38. Cryptanalysis of Image Cryptosystem Using Synchronized 4D Lorenz Stenflo Hyperchaotic Systems -- 39. Automatic Text-line level Handwritten Indic Script Recognition: A Two-Stage Framework -- 40. Weight based Secure approach for Identifying Selfishness behavior of node in MANET -- 41. Assisting Vehicles using Cyber Physical Systems -- 42. An efficient Framework based on segmented block analysis for human activity recognition -- 43. Ranked Gene Ontology based Protein Function Prediction by Analysis of Protein-Protein Interactions -- 44. Investigation of Optimal Cyclic Prefix length for 4G fading channel -- 45. High Density Noise Removal Algorithm for Brain Image Analysis -- 46. Pragmatic Study of Load Balancing in Parallel Architecture -- 47. A Novel Segmentation algorithm for feature extraction of Brain MRI Tumor -- 48. Adaptive Parameter Estimation Based Drug Delivery ystem for Blood Pressure Regulation -- 49. Mathematical Modelling of Sensitivity and Specificity for Basal Cell Carcinoma (BCC) Images -- 50.Integer Representation and B-Tree for Classification of Text Documents: An Integrated Approach -- 51. Switching angle and power loss calculation for THD minimization in CHB- Multilevel inverter using DEA -- 52. Load Balancing of Unbalanced Matrix with Summation Method -- 53. Detection of Outliers using Interquartile Range Technique from Intrusion Dataset -- 54. A Novel Arbitrary Oriented Multilingual Text Detection in Images/Video -- 55. Working with Cassandra Database -- 56. Learning to Solve Sudoku Problems with Computer Vision aided Approaches -- 57. Combined Effect of Cohort Selection and Decision Level Fusion in a Face Biometric System -- 58. Global Stability of Harvested Prey Predator Model with Infection in Predator Species -- 59. Flying Ad-hoc Networks : A Comprehensive Survey.
Keywords: Computational intelligence; Data mining; Artificial intelligence; Dynamics; Nonlinear theories; Application software; Computational Intelligence; Data Mining and Knowledge Discovery; Artificial Intelligence; Applied Dynamical Systems; Computer and Information Systems Applications